Adat Segulaha dalam Tradisi Masyarakat Kesultanan Ternate - Pettalongi, Sagaf S. (UIN Maulana Malik Ibrahim Malang, 2012)
Segulaha custom was a process of establishment and implementation of Ternate sultanate custom which was always obeyed and implemented by all the people of Ternate sultanate from the past time. The establishment of a custom was a joint agreement which becomes a guidance in managing socialization in all aspects for the interest of human prosperity. In implementing a custom, Ternate sultanate used bobato dunia system and bobato akhirat system as the organizer and director of custom convention/regulation and religious custom law. The major foundation of implementing segulaha custom began from seatorang custom, sekabasarang rules, galib se lukudi, ngare se cara sere se doniru and cing se cingari. Segulaha custom was implemented especially for joko kaha ceremony (injak tanah), crownprince coronation ceremony, sultanate inauguration ceremony (jou khalifah, jou kolano), and sultanate death ceremony. Segulaha custom was a form of combining of Islamic religious values and Ternate sultanate cultural values. Both values were integrated into one system of value which was sublimized by all people of Ternate sultanate North Maluku. Until this day, segulaha custom still implemented by the people of Ternate sultanate from generation to generation in cultural events. Adat segulaha adalah proses pembentukan dan pelaksanaan adat kesultanan Ternate yang sejak masa lampau selalu ditaaati dan dilaksanakan oleh segenap masyarakat kesultanan Ternate. Terbentuknya suatu adat istiadat merupakan kesepakatan bersama untuk dijadikan pedoman dalam mengatur pergaulan hidup di segala bidang guna mencapai kebahagiaan manusia. Dalam pelaksanaan adat istiadat kesultanan Ternate dikenal dengan sistem bobato dunia dan bobato akhirat sebagai pengatur dan pengarah undang-undang adat dan hukum adat agama. Dasar utama pelaksanaan adat segulaha bersumber dari adat se atorang, Istiadat se kabasarang, galib se lukudi, ngare se cara sere se doniru dan cing se cingari. Adat segulaha dilaksanakan terutama pada upacara joko kaha (injak tanah), upacara pengangkatan putra mahkota, upacara penobatan Sultan (jou khalifa jou kolano), dan upacara kematian sultan. Adat segulaha merupakan bentuk perpaduan antara nilai-nilai agama Islam dan nilai-nilai budaya kesultanan Ternate. Keduanya terintegrasi dalam satu sistem nilai yang dijunjung tinggi oleh segenap masayarakat kesultanan Ternate Maluku Utara. Sampai saat ini adat segulaha masih tetap dilaksanakan oleh masyarakat kesultanan Ternate secara turun temurun terutama dalam acara-acara kebudayaan.